Long term follow up of through-the-scope balloon dilation as compared to strictureplasty and bowel resection of intestinal strictures in crohn's disease - Krauss, Ekaterina; Agaimy, Abbas; Gottfried, Angelina; Maiss, Juergen; Weidinger, Thomas; Albrecht, Heinz; Hartmann, Arndt; Hohenberger, Werner; Neurath, Markus; Kessler, Hermann; Mudter, Jonas (International Journal of Clinical and Experimental Pathology, 2014)
Ileo-colonic strictures are common complication of Crohn's disease (CD), and may result in repeated endoscopic or surgical therapy with a risk of further complications, such as perforation or short bowel syndrome. Strictures develop as a consequence of tissue remodelling and fibrosis due to chronic inflammation. This study compares the outcome of CD patients undergoing primarily endoscopic treatment with those undergoing surgery at an university hospital.In this study we retrospectively included 88 CD patients with intestinal strictures (37 males, 51 females, mean age 40 years, range 19-65 years) of both our medical and our surgical department, who underwent either surgical or endoscopic therapy between January 2002 and January 2006 with prospective, controlled follow-up, extended till January 2010 (mean follow-up period: 5 years; range 4-8 years). The primary end-point was operation- and symptom-free time. Patients were primarily divided into four groups: only surgical therapy, only endoscopic therapy, endoscopy with subsequent surgery, and initial surgical therapy followed by endoscopic dilations.53% of all patients remained surgery-free with mean follow-up of 49 months; a single endoscopic dilation was sufficient enough in 9 patients to achieve a surgery-free time of 51 months, other patients required up to 5 dilations. The average interval between first and second dilation was 6.5 months, between second and third 10.5 months. In the group of patients with only endoscopic therapy, surgery- and symptom-free time was shorter, as compared to the group of only surgical therapy. We found that stenoses in the surgical group with an average length of 6.5 cm were as expected longer, as compared to the endoscopic group (3 cm, ranging from 2-4 cm). The surgery-free time was 49 months (42-71 months, P = 0.723) with a symptom-free time of 12 months (4.5-46 months, P = 0.921). In the group of only surgically treated patients, 68.4% of the patients had only one stenosis, 18.4% had 2-3 stenoses and 13.2% more than 3 stenoses. In all patients the surgery- and symptoms- free time was 69 months (57-83 months, P = 0.850 and 0.908). The other two groups showed similar results. We found no significant effect of characteristic of stenosis (length, inflammation, the number of stenoses), injection of prednisolone, disease activity at the time of dilation and medication at the time of dilation on the long-term outcome. Importantly, the success of symptom free time correlated with the diameter of the balloon.Endoscopic dilation should be considered as a first-line therapy for short, accessible, fibrotic strictures. Careful patient selection and proper diagnostic imaging pre-procedure are essential requirements for safe and successful treatment. The balloon diameter seems to correlate positively with the long term outcome of dilation. However, at ever shorter intervals between endoscopic interventions, surgery should be discussed as an option for further treatment.
EVALuna2:1853